The interventions of nutritional education on malnutrition infants mothers in Wonokromo Surabaya - Wiwik Afridah (Universitas Nahdlatul Ulama Surabaya, 2012)
Mother’s knowledge has great affect to the nutritional status of the infants, because mother has a big role in providing the food in the family. That Knowledge was heavily influenced by social circumstances of the family's such as lack of family income that may affect the mother's in providing the food in the family. The research objective is to examine the effect of nutrition education intervention on body weight of malnutrition infants in RW 07 Wonokromo, Surabaya. This study uses a pre-experimental study design with pre-post test type approach. The subjects were children aged six months to five years who are malnutrition and poor nutrition, with indexes BW/U is less than Z score, located in Wonokromo Village, Surabaya. Sampling techniques in a study conducted by simple random sampling. Analysis of differences nutritional status of children before and after giving of nutrition education were tested by paired t test (paired t test) and differences of mother’s knowledge before and after giving of nutrition education were tested by Wilcoxon signed rank test. Results of statistically tests by using a paired t-test obtained P Value (0.108) > α (0.05) means there is no different on giving of nutrition education intervention on weight infants in the RW. 07 Wonokromo Village, Surabaya. Results of statistically tests by using the Wilcoxon signed rank test obtained P Value (0.157) > α (0.05) means there is no different on giving of nutrition education intervention on parent’s knowledge level of a toddler in the RW. 07 Wonokromo Village Surabaya. Required planning and strategies to change behavior and awareness of nutrition and health. Using 4P concept for viewpoint of trainers/educators and 4C for viewpoint of participants or trained, and performed by ABC approach (Advocacy, Situation control and the Movement Atmosphere/mobilization).